2008
DOI: 10.21273/hortsci.43.2.505
|View full text |Cite
|
Sign up to set email alerts
|

Container Height and Douglas Fir Bark Texture Affect Substrate Physical Properties

Abstract: A study was conducted to quantify the effect of substrate texture on water-holding capacity of douglas fir [Pseudotsuga menziesii (Mirb.) Franco] bark (DFB) in containers of varying height. Medium (less than 2.2 cm) and fine (less than 0.9 cm) DFB were packed into 7.6 cm i.d. aluminum cores 3.8, 7.6, and 15.2 cm tall to determine container capacity (CC) and air space (AS) at varying container heights. Increasing container height resulted in a linear decrease in CC and a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 8 publications
2
36
1
1
Order By: Relevance
“…In addition to the inherent properties of a growing medium, container size and shape may have a marked influence on the air/water ratio of the substrate. In a pot or other container, a substrate moisture gradient exists where, due to gravitational effects, air content decreases and moisture increases from the top to bottom of the container (Fonteno, 1996; Owen and Altland, 2008). For example, in a 1:1 peat/vermiculite mixture filling containers 2.5 and 15 cm high, the air volume increased from 2 to 20% (Fonteno, 1988).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…In addition to the inherent properties of a growing medium, container size and shape may have a marked influence on the air/water ratio of the substrate. In a pot or other container, a substrate moisture gradient exists where, due to gravitational effects, air content decreases and moisture increases from the top to bottom of the container (Fonteno, 1996; Owen and Altland, 2008). For example, in a 1:1 peat/vermiculite mixture filling containers 2.5 and 15 cm high, the air volume increased from 2 to 20% (Fonteno, 1988).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The proportion of fine particles doubled for PB:PM and WPT:PM compared with PB and WPT, respectively. It has been reported that substrate particles less than 0.5 mm can have a significant effect on substrate air space and container capacity (Jackson et al, 2010;Owen and Altland, 2008). The greater proportion of fine particles most likely resulted in the greater substrate container capacity and lower substrate air space of the substrates amended with PM.…”
Section: Resultsmentioning
confidence: 99%
“…1). In addition to MRCs, the evaporation method has been used to describe hydraulic conductivity and substrate porosity (Fields et al, 2016(Fields et al, , 2017Naasz et al, 2005;Owen and Altland, 2008;Schindler, 1980;Schindler et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Moisture retention curve by frozen column method. The frozen column method was used to generate MRCs of the three substrates (peat, rockwool, and foam) at container capacity, with four replicates per substrate (Altland et al, 2010;Owen and Altland, 2008). Peat was filled into 3.8-cmdiameter clear plastic tubes of 30.5-cm length and dropped at a height of 6 cm three times to provide consistent compaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation